Obstetric complications in mothers with ADHD - Walsh, Caroline J.; Rosenberg, Sofie L.; Hale, Elijah W. (Frontiers in Reproductive Health, 2022)
Background: There is currently limited research on the intersection of pregnancy and ADHD and the unique pregnancy risk factors for mothers with an ADHD diagnosis. With an increased population of patients with ADHD in the recent decades and an increase in ADHD medication use during pregnancy it is important to consider what unique risks mothers with ADHD face during the perinatal period. Objective: Investigate a variety of outcomes in maternal ADHD. Methods: We identified female patients with a diagnosis of pregnancy and ADHD diagnosis. We also further separated the ADHD cohort for separate sub-analyses based on medication type. Odds ratios and relative risk were calculated from outcome incidence within each cohort. Cohorts were balanced on age, sex, and race. Results: We identified 45,737 pregnant females with ADHD. We matched these patients to pregnant females without ADHD, for a total of 42,916 pairs. Compared to the group without ADHD, mothers with ADHD had higher rates of every outcome except for HPV infection, which was statistically insignificant (p=0.768). The odds ratios ranged from 1.08 for anemia complicating pregnancy to 2.63 for depressive episodes. Most outcomes were between 1.2 and 1.8 times more likely to occur in the cohort with ADHD. Conclusion: This study presents substantial advancements in our knowledge of pregnancy-related ADHD care. Armed with an increased awareness of these potential complications and their relationship with ADHD, obstetricians, psychiatrists, and providers of all specialties may be able to reduce the rate of complications within this specific patient population.